The Influence of the Learning Environment on Students' Motivation to Learn Mathematics - Robert Harianja; Taruly Tampubolon (Jurnal Penelitian Pendidikan IPA, 2025)
The learning environment plays a crucial role in shaping students' motivation, especially in mathematics, a subject that often triggers anxiety and demands high reasoning skills. This study aims to analyze the influence of the learning environment's physical, social, and emotional dimensions on students' motivation to learn mathematics at SMPN 4 Siborongborong, a rural school with unique challenges. Using a quantitative explanatory approach with a cross-sectional design, data were collected from 30 eighth-grade students through adapted and validated instruments: the What Is Happening In this Class? (WIHIC) questionnaire for learning environment and the Academic Motivation Scale (AMS) for learning motivation. Data were analyzed using multiple linear regression with SPSS version 25. The findings reveal that the emotional dimension of the learning environment significantly affects students' motivation (β = 0.347; p < 0.05), while the physical and social dimensions do not show statistically significant effects. The model explains 53.2% of the variation in learning motivation, indicating a strong relationship between the learning environment and student motivation. The results underscore the importance of fostering a favourable emotional climate in the classroom to enhance engagement and reduce math-related anxiety. These findings contribute to developing evidence-based strategies to improve mathematics learning outcomes in rural educational settings.